STUDENTS' PERSPECTIVES ON MOTIVATION TO LEARN ENGLISH - Nihta v.F. Liando (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
Improving learning outcomes has always been the target of the foreign language learning practices. The central role of students in the learning process had attracted researchers to conduct research in order to increase students' success in learning. Student motivation is considered one of the factors contributing to students' success in learning a foreign language. Although there is a large body of research on motivation in second/foreign language learning, most studies were undertaken in Western contexts. There is still only a relatively small amount of research on motivation in second/foreign language learning in Asian contexts, particularly in the Indonesian context. This study investigated the motivational factors that influence first year university students' performance studying English as a foreign language (EFL) as their major. A questionnaire adapted from Gardner (J985), consisting of a range of motivational scales that have been widely used in studies on motivation, was utilized and students' demographic information was collected.